S-nitrosylation influences the structure and DNA binding activity of AtMYB30 transcription factor from Arabidopsis thaliana - Tavares, Carolina Pereira (2014)
MYB proteins are a family of transcription factors that play an important role in plant development and regulatory defense processes. Arabidopsis thaliana MYB30 (AtMYB30), a member of this protein family, is involved in cell death processes during the hypersensitive response (HR) of plants. HR is characterized by a vast production of reactive oxygen species (ROS) and nitric oxide (NO). NO may thus influence the binding of AtMYB30 to DNA. In this work we evaluated the effect of NO on AtMYB30 DNA binding activity, and also in the protein structural properties. A fully active minimal DNA-binding domain (DBD) of AtMYB30 (residues 11–116) containing two cysteine residues (C49 and C53) was overexpressed and purified. Site-directed mutagenesis was used to obtain AtMYB30 DBD mutants C49A and C53A. The DNA binding activity of AtMYB30 DBD, and Cys single mutants is clearly inhibited upon incubation with a NO donor, and S-nitrosylation was confirmed by the biotin switch assay. Finally, in order to understand the mechanism of NO effect on AtMYB30 DNA binding activity we performed circular dichroism analysis, to correlate the observed protein function inhibition and a potential structural impairment on AtMYB30 DBD. Indeed, NO modification of C49 and C53 residues promotes a subtle modification on the secondary structure of this transcription factor. We thus demonstrated, using various techniques, the in vitro effect of NO on AtMYB30 DBD, and thus the potential consequences of NO activity on plant metabolism influenced by this transcription factor.